Desarrollo de un curso virtual en la plataforma moodle como apoyo didáctico en la enseñanza aprendizaje del bloque curricular funciones y ecuaciones lineales y cuadráticas de la asignatura de Matemática, para los estudiantes de primer año de bachillerato general unificado del colegio de bachillerato 27 de Febrero de la ciudad de Loja, período 2014-2015 - Zhigui Armijos, Doris Leonor (2016)
This research work refers to the lack of an educational resource for the learning teaching of mathematics from students of the First year of Bachillerato General Unified “27 de Febrero” school of the Loja city. Faced to this problem was created a virtual training course about curricular block one of functions and linear and quadratic equations, and material support teaching-learning process is proposed, and thus way reinforce student learning. For the preparation of resource was applied the waterfall methodology. In the phase of analysis was required a diagnostic test which was performed to students, an interview to the teacher who helped to identify the weaknesses in the process of teaching- learning of the mathematics the same that were solved with the development of virtual course where include (main contents, videos, activities, assessments and tasks/homework of the virtual course) .In the verification phase was established that users consider online course is effective, come across the necessary educational and pedagogical features and technology necessaries where the objectives were raised. To conclude that it is necessary to incorporate the virtual course made the teaching- learning process of the mathematics subject, as it is a teaching tool that helps to fulfill the content, objectives and curricular skills. Therefore it is recommended to the education authorities implement virtual courses to improve the teaching-learning process